Interactions between hypocretinergic and GABAergic systems in the control of activity of neurons in the cat pontine reticular formation. (9th July 2015) - Xi, M.; Fung, S.J.; Yamuy, J.; Chase, M.H.
Highlights: We examined the response of NPO neurons following the application of hypocretin-1 and GABA. Hypocretin-1 excites NPO neurons, and GABA inhibits NPO neurons. The inhibitory effect of GABA is reduced by hypocretin-1. The occurrence of REM sleep depends upon interactions between hypocretin and GABA. Abstract: Anatomical studies have demonstrated that hypocretinergic and GABAergic neurons innervate cells in the nucleus pontis oralis (NPO), a nucleus responsible for the generation of active (rapid eye movement (REM)) sleep (AS) and wakefulness (W). Behavioral and electrophysiological studies have shown that hypocretinergic and GABAergic processes in the NPO are involved in the generation of AS as well as W. An increase in hypocretin in the NPO is associated with both AS and W, whereas GABA levels in the NPO are elevated during W. We therefore examined the manner in which GABA modulates NPO neuronal responses to hypocretin. We hypothesized that interactions between the hypocretinergic and GABAergic systems in the NPO play an important role in determining the occurrence of AS or W. To determine the veracity of this hypothesis, we examined the effects of the juxtacellular application of hypocretin-1 and GABA on the activity of NPO neurons, which were recorded intracellularly, in chloralose-anesthetized cats. The juxtacellular application of hypocretin-1 significantly increased the mean amplitude of spontaneous EPSPs and the frequency of discharge of NPO neurons; in contrast, the juxtacellular microinjection of GABA produced the opposite effects, i.e., there was a significant reduction in the mean amplitude of spontaneous EPSPs and a decrease in the discharge of these cells. When hypocretin-1 and GABA were applied simultaneously, the inhibitory effect of GABA on the activity of NPO neurons was reduced or completely blocked. In addition, hypocretin-1 also blocked GABAergic inhibition of EPSPs evoked by stimulation of the laterodorsal tegmental nucleus. These data indicate that hypocretin and GABA function within the context of a neuronal gate that controls the activity of AS-on neurons. Therefore, we suggest that the occurrence of either AS or W depends upon interactions between hypocretinergic and GABAergic processes as well as inputs from other sites that project to AS-on neurons in the NPO.